Efectos del canal del crédito sobre el precio de la vivienda nueva en Medellín - Colombia; Credit channel effects on new residential property prices: Evidence from Medellín, Colombia - John Jairo García Rendón; Daniel Mateo Cossio Sepúlveda; Ricardo Mesa Urhan (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
– We analyze the credit channel effects on new residential property prices in Medellín, Colombia, using a simultaneous equations model. Our empirical results show that the main determinants of new residential properties prices are mortgage interest rates and the availability of government sponsored subsidies to homebuyers (GS). An increase of one percent in mortgage interest rates reduces the demand of new residential properties and increases their price by COP 46,865 per square meter. Greater availability of government of GS increases the demand for new residential properties. Using a structural VAR, we find that a positive shock to a proxy for the real interest rate (unit of real value, URV) of one standard deviation leads to a reduction of the price of new residential properties in Medellín.
Keywords: D43; L16; L74; 330; New housing; supply and demand model; URV; SVAR; SUR; 3SLS Medellin; Colombia